Real Exchange Rates and Commodity Prices in Neoclassical Model. (IMF Working Papers; Working Paper ;, 1988)
This paper presents a neoclassical model that explains the observed empirical relationship between government spending and world commodity supplies and the real exchange rate and real commodity prices. It is shown that fiscal expansion and increasing world commodity supplies simultaneously lead to an appreciation of the real exchange rate and a decline in relative commodity prices. This structural model is estimated and its forecasting performance is compared to a variety of models. We find that theory and structure help in predicting commodity prices, although not the exchange rate, and that predictive ability increases as the forecast horizon is lengthened. MASTER FILES ROOM C-130 001.